DEVELOPMENT OF LEARNING MEDIA USING GOOGLE SITES TO IMPROVE STUDENTS' ABILITIES - Aisyah, St.; Syarifuddin, Syarifuddin; Triana, Yuli (Universitas Lambung Mangkurat, 2023)
The development of online learning media is increasingly important in today's digital era, especially during the COVID-19 pandemic which forced the process of distance learning. This study aims to develop learning media using Google Sites and evaluate its effect on students' abilities in terms of understanding the material and practical skills. The literature study method was used to evaluate the results of previous similar studies and provide a broader understanding of this topic. The results of the study show that the development of online learning media using Google Sites can improve students' abilities in terms of understanding material and practical skills, using technology that is familiar to students can increase their learning motivation. This study also compares the results with previous similar studies, including research that examined offline learning media. This helps provide a broader understanding of the advantages and disadvantages of online and offline learning media. In conclusion, the development of online learning media using Google Sites can be an effective alternative for distance learning during the COVID-19 pandemic. However, it should be noted that the use of online learning media does not completely replace the use of offline learning media. Further research with a larger and more diverse sample is recommended to generalize the results of this study more broadly.